Biochemical degradation and physical migration of polyphenolic compounds in osmotic dehydrated blueberries with pulsed electric field and thermal pretreatments - Yu, Yuanshan; Jin, Tony Z.; Fan, Xuetong; Wu, Jijun (Food chemistry, 2018)
•Fresh blueberries were pretreated by pulsed electric field before osmotic dehydration.•Pretreatment significantly reduced the dehydration time of blueberry samples.•Pretreated samples had the least biochemical degradation.•Pretreated samples maintained high levels of nutritive compounds.•Pretreated and dehydrated fruits showed superior appearance to control samples. Fresh blueberries were pretreated by pulsed electric fields (PEF) or thermal pretreatment and then were subject to osmotic dehydration. The changes in contents of anthocyanins, predominantly phenolic acids and flavonols, total phenolics, polyphenol oxidase (PPO) activity and antioxidant activity in the blueberry samples during pretreatment and osmotic dehydration were investigated. Biochemical degradation and physical migration of these nutritive compounds from fruits to osmotic solutions were observed during the pretreatments and osmotic dehydration. PEF pretreated samples had the least degradation loss but the most migration loss of these compounds compared to thermally pretreated and control samples. Higher rates of water loss and solid gain during osmotic dehydration were also obtained by PEF pretreatment, reducing the dehydration time from 130 to 48h. PEF pretreated and dehydrated fruits showed superior appearance to thermally pretreated and control samples. Therefore, PEF pretreatment is a preferred technology that balances nutritive quality, appearance, and dehydration rate.